Farmers’ socioeconomic characteristics and perception of land use change defining optimal agroforestry practices in Khost Povince, Aghanistan - Ahmadzai, Mujib Rahman; Ismail, Mohd Hasmadi; Hassan Zaki, Pakhriazad; Magiman, Mohd. Maulana; Bawon, Paiman (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Agroforestry practices evolve with the development of basic and advanced facilities, changes in natural and artificial factors of land, and land use trade-offs. This study aims to examine the farmers’ socioeconomic characteristics and perception of land use changes that define optimal agroforestry practices in Khost Province, Afghanistan. Data were collected from 662 farmers and analyzed using univariate Analysis of Variance (ANOVA) and Multivariate Analysis of Variance (MANOVA). The results found that forest and vegetable products, including fruits, berries, herbs, mushrooms, wild animals, oils, wood, honey, okra, eggplant, carrot, cucumber, pine nuts, pepper, and timber, have different impacts in terms of satisfaction with basic and advanced facilities, knowledge of land use changes, satisfaction with natural and artificial resources of land, and barriers to and economic benefits of land use. The limitations of this study included an absence of exogenous factors in the model such as climate change, financial conditions, market fluctuations, regulatory system, the area in which this study is selected, research design, and current condition of endogenous factors. Overall, this study defined a set of optimal agroforestry practices (expressed as crops and products) based on the farmers’ perception of land use changes in Khost Province, Afghanistan. This study provided useful insights for policymakers and development practitioners to promote agroforestry practice adoption and improve the socioeconomic development of agroforestry-dependent communities. Future works could explore the implications of agroforestry practices on the socioeconomic development of other dependent communities in Afghanistan.